Curvature of a line defined as a discrete set of points, and diffraction pattern processing for laser ektacytometry of red blood cells. (September 2019) - Nikitin, S.Yu.; Ustinov, V.D.; Shishkin, S.D.
Highlights: A new procedure for processing diffraction patterns is proposed, based on the notion of a band point. The curvature of the isointensity line is measured with an error of less than one percent. Video camera resolution of at least 10 megapixels required. Abstract: The problem of measuring the erythrocyte deformability by laser diffractometry in a shear flow (ektacytometry) is considered. A procedure for processing diffraction patterns is proposed, which makes it possible to measure the curvature of the isointensity lines with high accuracy. The procedure involves finding the specific points of the isointensity line, which we called the band points. The coordinates of these points are determined by the isointensity line (band) width, depending on the resolution and dynamic range of the camera. Determining the coordinates of the band points allows us to calculate the curvature of the line by the formula of the second differential derivative. The accuracy of the procedure is justified with the help of analytical estimates of the second and fourth derivatives of the function describing the isointensity line. It is shown that to measure the curvature of the isointensity line with an error not exceeding one percent, it is necessary to photograph the neighborhoods of the points of interest to us with a resolution of about 10 megapixels or to take an image of the entire diffraction pattern with a resolution of 100 megapixels.